Strategi Peningkatan Kualitas Pendidikan dan Responsivitas Darurat Sosial Melalui Perencanaan Kontinjensi pada UIN K.H. Abdurrahman Wahid Pekalongan - Ghozani, Sobi (JURNAL ILMIAH GEMA PERENCANA, 2025)
This Policy Paper explains that improving the quality of education is determined by various factors, namely curriculum, materials, research, and the role of universities in community development and development. However, to realize this is hampered by a management system that is not ready to face changes and emergency conditions. The purpose of this study is to build a contingency planning strategy to support universities in improving the quality of education through their participation in society and development, especially in terms of participation in overcoming social emergencies. This study was conducted using a qualitative approach. The data used in this study are primary data, namely observations and secondary data through reports, journals, and other written documents. The results show that: 1) the success of universities in improving the quality of education is also reviewed from the role and relevance of their research in dealing with crucial issues in society so that universities will become a reference in decision-making; 2) the way to increase the role of universities is through contingency planning so that the role and relevance of research are adjusted to crucial problems that arise suddenly or their role in helping to participate in overcoming social emergencies in society; and 3) to build a contingency planning strategy, collaboration can be carried out between PESTEL analysis which reviews external elements and Resource Based View analysis which reviews potential resources in higher education.